The Effect of Ficus Religiosa Chloroform Extract on Suppression of Acquired Docetaxel Resistance in Prostate Cancer - Ibrahim, Niran A. (Iraqi Journal of Cancer and Medical Genetics, 2013)
Most of the currently used cancer therapeutics are natural products. These agents were generally discovered based on their toxicity to cancer cells using various bioassays. Ficus religiosa (FR) plant is important medicinal plant and traditionally used to treat various diseases including mastitis, otitis media, pharyngolaryngitis, urethritis, dysmenorrhea and diabetic. Accordingly, it was aimed to investigate the cytotoxic effect of Ficus religiosa chloroform extract on Patch1 and Gli2 gene expression in Hedgehog pathway and Id1, Id2 and Id3 genes expression in inhibition differentiation pathway on prostate cancer cells, which are resistance to docetaxel (PC3-TxR) in vitro. Chloroform extract of Ficus religiosa plant leaves was performed to tested cytotoxic effect on PC3-TxR by using Sulforhod-amine-B assay and its ability to inhibition genes expression on PC3-TxR cells by using RT-PCR assay. The results showed that F. religiosa chloroform extract display high cytotoxic effect (IC50= 0.3±0.02 mg/ml), and inhibition effect of Id2 and Id3 gene expression more than, Patch1 and Gli2 gene expression on PC3-TxR cells. The present study showed anticancer effect of F. religiosa chloroform extract which target Id pathway on PC3-TxR cells.